Evaluation of Drainage Channels on Residential Area - O.T. Ikotun; Dewi Sartika (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2019)
The incompatibility of construction of urban or residential drainage channels with design criteria is often found due to difficulties in designing drainage channels. designers often make design mistakes when designing drainage channels. This study aims to evaluate the drainage system and designs a drainage channel that can collect runoff discharge on Residential Area. The results of flood discharge obtained using the Gumbel method for the 10 and 25 year return periods are 298.78 mm and 370.38 mm. From the calculation of the channel capacity in the field and the discharge plan most of the existing channel capacity cannot accommodate the current planned discharge of 2.261 m3s-1 for the primary channel and 1.824 m3s-1 for the secondary channel. The current channel cannot accept runoff discharge during rain, so the channel rehabilitation plan is carried out by expanding and extracting the dimensions of the drainage channel.